2019
DOI: 10.1093/bjsw/bcz137
|View full text |Cite
|
Sign up to set email alerts
|

Children in Care: Exploitation, Offending and the Denial of Victimhood in a Prosecution-led Culture of Practice

Abstract: The following article reports upon recent research, which explored the perceptions of professionals of the issues that affect the sexual and criminal exploitation of children in care, along with a discussion of the effectiveness of current responses to these issues and the challenges that professionals face. The study utilised focus groups and semi-structured interviews to gain the perspectives of thirty-six participants from across a range of agencies involved in children’s social work and youth justice from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The study of juvenile crime early warning management promotes the integration of juvenile crime issues into the social early warning system and provides a new perspective and platform for juvenile crime prevention and reduction efforts. In terms of space, we will model the coordination and unification of several social management subsystems that are highly relevant to the development of youth education, such as comprehensive governance, public security, and political and legal affairs [ 2 ]. In terms of time, we will grasp the opportunity to prevent crime before it happens, take the initiative to carry out a targeted advance in advance, and transform the correction afterward into prevention and intervention beforehand; in terms of degree, we will establish a deep prevention and control pathway and through cooperation.…”
Section: Introductionmentioning
confidence: 99%
“…The study of juvenile crime early warning management promotes the integration of juvenile crime issues into the social early warning system and provides a new perspective and platform for juvenile crime prevention and reduction efforts. In terms of space, we will model the coordination and unification of several social management subsystems that are highly relevant to the development of youth education, such as comprehensive governance, public security, and political and legal affairs [ 2 ]. In terms of time, we will grasp the opportunity to prevent crime before it happens, take the initiative to carry out a targeted advance in advance, and transform the correction afterward into prevention and intervention beforehand; in terms of degree, we will establish a deep prevention and control pathway and through cooperation.…”
Section: Introductionmentioning
confidence: 99%
“…Their experience confirmed that positive relationships, based on trust, are important in developing resilience for traumatised young people in residential care (Luthar, 2000;Mota et al, 2016). Previous research has shown that young people often hold negative opinions about police (Brunson & Weitzer, 2009;Carr et al, 2007;Day, 2017;Shaw, 2017;Shaw & Greenhow, 2020) and tend to be resistant towards police and reluctant to seek help from them (Kirk & Matsuda, 2011;Tyler et al, 2014). The participants in this study reported that some young people began to trust members of the police and reach out to them for assistance.…”
Section: Discussionmentioning
confidence: 73%
“…CCE requires a comprehensive safeguarding response rooted in the public health ethos of early intervention and prevention that duly incorporates and acknowledges the systemic predisposing preconditions for both victims and perpetrators, and the duality of these roles. This approach highlights the nuances of victimisation, however, the identification of characteristics of to a different agenda: linear criminal justice approaches reduce youth offending to identification of the offence and the perpetrator, but fail to explore the offence as symptomatic of other causes including social pressures or coercive control by organised crime (Shaw & Greenhow, 2020;Sturrock & Holmes, 2015).…”
Section: Child Poverty: Cce Drugs and Public Healthmentioning
confidence: 99%
“…The contextual safeguarding approach enables us to have a wider perspective and insight of the situations and relationships in which CCE is likely to manifest. Public health and social care responses to CCE do not converge with the criminal justice response which runs in parallel, to a different agenda: linear criminal justice approaches reduce youth offending to identification of the offence and the perpetrator, but fail to explore the offence as symptomatic of other causes including social pressures or coercive control by organised crime (Shaw and Greenhow, 2020; Sturrock and Holmes, 2015).…”
Section: Introduction: a New Model For Understanding Child Criminal E...mentioning
confidence: 99%